Resveratrol reduces inflammatory response and detrimental effects in chronic cerebral hypoperfusion by down-regulating stimulator of interferon genes/TANK-binding kinase 1/interferon regulatory factor 3 signaling - Kang, Ning; Shi, Yuanyuan; Song, Jiaxi; Gao, Fei; Fan, Mingyue; Jin, Wei; Gao, Yaran; Lv, Peiyuan (Frontiers in Aging Neuroscience, 2022)
Inflammatory responses induced by chronic cerebral hypoperfusion (CCH) play a critical role in the progression of vascular dementia. Stimulator of type 1 interferon gene (STING) signaling functions as a key mediator of inflammation and immunological responses in the central nervous system (CNS), and Resveratrol exerts potent anti-inflammatory effects. However, the role of STING signaling and the relationship between Resveratrol and STING signaling in persistent hypoperfusion-induced cerebral inflammation remain unclear. In this study, Sprague-Dawley rat were subjected to either Sham or bilateral common carotid artery occlusion (2VO) surgery and received Resveratrol or vehicle daily by intraperitoneal injection for 4 or 8 weeks. Morris water maze was used for analysis of cognitive function. The neuroinflammatory responses in white matter and hippocampus of the rat brain were assessed by Western blot, Immunofluorescence staining, and Quantitative real-time PCR analyses. Myelin integrity, neutrophil infiltration and microglia proliferation were assessed by Immunohistochemistry and histologic analysis. We demonstrated that after CCH, neuron, microglia and astrocyte under endoplasmic reticulum (ER) stress upregulated the expression of STING, TANK-binding kinase 1 (TBK1) and the transcription factor interferon regulatory factor 3 (IRF3), as well as translocation of IRF3 into nucleus. These were accompanied by infiltration of neutrophils, activation of microglia and overproduction of proinflammatory mediators. Improvements in cognitive deficits were related to reduced hippocampal neuronal cell death and increased myelin integrity in Resveratrol-treated rat. The neuroprotective effects of Resveratrol were associated with suppression of the expression of TNF-α, ICAM-1, interferon-β(IFN-β) and IL-1β, likely through mitigation of the STING/TBK1/IRF3 pathway. These inhibitory effects exerted by Resveratrol also inhibited the levels of myeloperoxidase, reduced excess expression of reactive astrocytes and activated microglia. In conclusion, the STING/TBK1/IRF3 axis may be critical for proinflammatory responses in cerebral tissue with persistent hypoperfusion, and Resveratrol exerts its anti-inflammatory effects by suppressing STING/TBK1/IRF3 signaling.